Implementasi Layanan Pengembangan Anak Usia Dini Holistik Integratif Pada Lembaga Paud Tk. Negeri Pembina Sekadau Hilir - Minawasti Minawasti; Martoyo Martoyo; Yulius Yohanes (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the implementation of Holistic Integrative Early Childhood Development (PAUD HI) services at TK Negeri Pembina Sekadau Hilir, Sekadau Regency. The focus of this study is to identify supporting and inhibiting factors in the implementation of the program, as well as to evaluate the impact of the program on early childhood development in this institution. The approach used is a qualitative method with data collection techniques through in-depth interviews, field observations, and documentation. The results of the study indicate that the implementation of PAUD HI at TK Negeri Pembina Sekadau Hilir went quite well, although there were several obstacles such as limited understanding of educators regarding the holistic integrative concept, limited facilities and infrastructure, and limited human resources. Factors that support the successful implementation of this program include support from the local government, active participation of parents, high commitment from educators, and good cooperation with local health institutions. The positive impact of this program is seen in the improvement of children's development in cognitive, social-emotional, physical, and character aspects. This study makes an important contribution to the development of more holistic and integrative early childhood education policies. It is expected that the results of this study can be a reference for local governments, educational institutions, and communities in improving the quality of PAUD services in other areas.